Transforming subsistence farmers into market-connected entrepreneurs - Mimm, Chris (Technical Centre for Agricultural and Rural Cooperation, 2018)
Chris Mimm explains how Farmshine is attempting to rebuild the value chain infrastructure in East Africa. Farmshine connects actors in the value chain on a fully transparent blockchain platform, providing them with a digital identity and fully traceable record of transactions.